Codeswitching practices of lecturers and students in an institute of higher education in Pakistan / Mujahid Shah - Mujahid , Shah (2018)
Multilingual practices, such as codeswitching (CS), have been widely explored both from grammatical and sociolinguistic perspectives. However, an exploration of CS from a micro-macro integrated sociolinguistic perspective has been neglected. Pakistan, being a multilingual country, is home to bilingual and multilingual practices, such as CS, but unfortunately these have not been fully explored, and in cases that involve local languages such as Pashto, there is a dearth of research. Therefore, the current study aimed to investigate the types, and reasons for CS, and the use of CS as a resource for identity formation in a group of lecturers’ and students’ interactive practices in an institute of higher education in Pakistan. Data were collected through ethnographic observations, recordings of interactions between lecturers and students and via semi-structured interviews, and then ethnographically analyzed. The findings showed the emergence of three types of CS, Inter, Intra and Tag CS, with diverse forms and patterns. The Inter, Intra and Tag CS are triggered by micro-macro reasons such as unconscious or habitual uses, solidarity, social status and emotional expressions which could be linked to socio-cultural, socio-psychological and communicative factors. In relation to an identity dimension, it was found that micro attributes and identities led to the formation of macro identities such as ethnic, social and hybrid bilingual identities of the speakers. The study is also important in the sense that CS has been approached from a multilingual perspective as proposed by MacSwan (2017). In the Pakistani context, the study can help trigger similar kinds of research and thus, further our understanding about multilingualism and the use of other local languages.